2006
DOI: 10.2174/138161206775474314
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Inhibition: A Therapeutic Strategy Targeting Multiple Disease States

Abstract: The calpains represent a well-conserved family of calcium-dependent cysteine proteases. They consist of several ubiquitous and tissue specific isoforms and exhibit broad substrate specificity influencing many aspects of cell physiology including migration, proliferation and apoptosis. Calpain activity in vivo is tightly regulated by its natural endogenous inhibitor calpastatin. Calpastatin specifically inhibits calpain and not other cysteine proteases by interaction with several sites on the calpain molecule. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
150
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 205 publications
(311 reference statements)
2
150
1
1
Order By: Relevance
“…BDA‐410 is a synthetic Leu‐Leu peptidomimetic that significantly attenuates various disease conditions (Carragher, 2006), including memory and synaptic transmission in a mouse model of Alzheimer disease and signs of premature aging in a mouse model of kotho deficiency (Manya et al ., 2002; Trinchese et al ., 2008). BDA‐410 strongly and reversibly inhibits cysteine proteases but not serine or aspartic proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…BDA‐410 is a synthetic Leu‐Leu peptidomimetic that significantly attenuates various disease conditions (Carragher, 2006), including memory and synaptic transmission in a mouse model of Alzheimer disease and signs of premature aging in a mouse model of kotho deficiency (Manya et al ., 2002; Trinchese et al ., 2008). BDA‐410 strongly and reversibly inhibits cysteine proteases but not serine or aspartic proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have clearly shown that ROCK inhibition completely abolishes macrophage migration through fibrillar collagen. One explanation could be that -in contrast to tumour cells such as HT1080, which can employ mesenchymal migration in either loose or dense matrices (Carragher, 2006;Friedl and Wolf, 2003) -amoeboid migration is the default migration mode of macrophages in fibrillar collagen, whereas mesenchymal migration is only triggered by the contact of macrophages with dense matrices and could require additional effectors that are not expressed during amoeboid migration or upon macrophage contact with loose matrices. So, although ROCK inhibition induces an elongated macrophage morphology, this is not sufficient to trigger macrophage mesenchymal migration in fibrillar collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, caspase 1-mediated activation of calpains in the absence of HMGB1 led to the inflammation and apoptosis seen in this model. Calpain activation does not degrade target proteins but rather cleaves them into stable fragments with functions that are different from the parent protein (37). The calpain proteases are ubiquitously expressed and play roles in cell division, cell movement, signal transduction, and apoptotic pathways (26).…”
Section: Il10mentioning
confidence: 99%